Interviews and assessments of returning non-compliant periodontal maintenance patients - Fardal (journal of clinical periodontology, 2006)
Background: Periodontal therapy without a maintenance programme has been shown to be of doubtful value. Most studies show a low-level of compliance with periodontal maintenance therapy. Many suggestions as to the reasons for this have been put forward, but it has been difficult to confirm these, as the patients are not available to be interviewed. Aim: To identify, interview and assess returning non-compliant periodontal maintenance patients. Method: All patients who had undergone periodontal therapy between 1986 and 2004 but not complied with the maintenance therapy were interviewed and assessed when they later returned to the specialist office for treatment. Results: Sixty-one patients with an average age of 56.4 years (SD 11,1) were studied. There were 18 males and 43 females. The patients were compliant for 3.4 years (SD 3.2) before leaving and returning after 5.5 years (SD 3.3) of non-compliance. Average tooth loss while non-compliant was 1.6 teeth (SD 2.8). The interviews revealed that 37 patients attended their own dentist’s office exclusively for maintenance therapy, eight patients gave health reasons and seven patients lack of motivation or failure to cooperate. Thirty-six patients were re-referred by their own dentist, 13 changed dentist and were referred by this dentist, while 12 patients contacted the specialist office directly. Fifty-three patients claimed to have been fully compliant with their own dentist while non-compliant with the specialist office. Conclusion: The main reason for non-compliance was that the patients did attend their own dentist exclusively for maintenance therapy. Tooth loss and periodontal deterioration was more marked in this group than patients who in addition attended the specialist office for maintenance therapy.